2021
DOI: 10.1093/jalm/jfaa233
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Mass Spectrometry Platform for IDH Mutation Status Prediction, Glioma Diagnosis, and Estimation of Tumor Cell Infiltration

Abstract: Background Surgical tumor resection is the primary treatment option for diffuse glioma, the most common malignant brain cancer. The intraoperative diagnosis of gliomas from tumor core samples can be improved by use of molecular diagnostics. Further, residual tumor at surgical margins is a primary cause of tumor recurrence and malignant progression. This study evaluates a desorption electrospray ionization mass spectrometry (DESI-MS) system for intraoperative isocitrate dehydrogenase (IDH) mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 35 publications
4
27
0
Order By: Relevance
“…Although there are some liquid chromatography coupled to mass spectrometry systems that are CE-IVD (i.e., European directive for In Vitro Diagnostics) approved for clinical biochemistry, toxicology, or therapeutic drug monitoring, and mass spectrometers can be used in operating rooms [139,140], not all medical laboratories are and will be equipped with mass spectrometers (especially high-resolution instruments) and very few of them with nuclear magnetic resonance instruments. Thus, other analytical methods, such as enzyme assays, immunoassays, and biosensors, have to be envisaged for metabolite detection.…”
Section: Metabolomics At Medical Laboratoriesmentioning
confidence: 99%
“…Although there are some liquid chromatography coupled to mass spectrometry systems that are CE-IVD (i.e., European directive for In Vitro Diagnostics) approved for clinical biochemistry, toxicology, or therapeutic drug monitoring, and mass spectrometers can be used in operating rooms [139,140], not all medical laboratories are and will be equipped with mass spectrometers (especially high-resolution instruments) and very few of them with nuclear magnetic resonance instruments. Thus, other analytical methods, such as enzyme assays, immunoassays, and biosensors, have to be envisaged for metabolite detection.…”
Section: Metabolomics At Medical Laboratoriesmentioning
confidence: 99%
“…Spatial tissue analysis has been possible by the development of several imaging methodologies, for example, DESI-MSI, LAESI, and MALDESI. Out of many, DESI is the most used for chemical imaging and intraoperative diagnosis of tissue samples [101][102][103]. In the majority of analyzed clinical samples, lipid species encompassing different classes, such as fatty acids and glycerophospholipids, were observed as the discriminating molecules in cancer vs. normal tissue comparison.…”
Section: Trends Trends In In Molecular Molecular Medicine Medicinementioning
confidence: 99%
“…The issue of spatial resolution (often not at single cell levels in prominent ambient MS methods) causes sensitivity of signal to tumour cellularity, as shown in a DESI-MS lipidomic profiling study of brain cancers [95] and the localization of high 2-hydroxyglutarate (2HG) signal levels in the regions of glioblastoma tumours with a dense cellularity [10]. While this sensitivity can be utilized to estimate tumour cell percentage [96], which is in its own right a useful clinical indicator currently only obtainable by time consuming histologic staining and microscopy, caution must be exercised in the interpretation of ambient MS profiles associated with residual disease presence. Residual HER2 expression within breast tumours [97] in a proteomic MALDI-MS study has been shown to influence receptor status predictions [98].…”
Section: Molecular Heterogeneities In Biological Tissues Impact Metabolome and Lipidome Profilesmentioning
confidence: 99%